Species dispersal and biodiversity in human-dominated metacommunities. (14th November 2018) - Shanafelt, David W.; Clobert, Jean; Fenichel, Eli P.; Hochberg, Michael E.; Kinzig, Ann; Loreau, Michel; Marquet, Pablo A.; Perrings, Charles
Highlights: Biodiversity may increase with dispersal or be maximized at an intermediate level. Dispersal-diversity relationship depends on ecological and economic parameters. Inclusion of non-consumptive benefits changes harvest regime. Abstract: The concept of the Anthropocene is based on the idea that human impacts are now the primary drivers of changes in the earth's systems, including ecological systems. In many cases, the behavior that causes ecosystem change is itself triggered by ecological factors. Yet most ecological models still treat human impacts as given, and frequently as constant. This undermines our ability to understand the feedbacks between human behavior and ecosystem change. Focusing on the problem of species dispersal, we evaluate the effect of dispersal on biodiversity in a system subject to predation by humans. People are assumed to obtain benefits from (a) the direct consumption of species (provisioning services), (b) the non-consumptive use of species (cultural services), and (c) the buffering effects of the mix of species (regulating services). We find that the effects of dispersal on biodiversity depend jointly on the competitive interactions among species, and on human preferences over species and the services they provide. We find that while biodiversity may be greatest at intermediate levels of dispersal, this depends on structure of preferences across the metacommunity.